2010
DOI: 10.2190/em.29.1.e
|View full text |Cite
|
Sign up to set email alerts
|

Finding Movies Interesting: How Appraisals and Expertise Influence the Aesthetic Experience of Film

Abstract: Film and television are major parts of everyday aesthetic experience, but not much is known about viewers' aesthetic experience of motion picture media. We explored how interest and confusion in response to film were predicted by people's cognitive appraisals and level of expertise. People who varied in expertise viewed 10 film clips taken from submissions to a local film festival. For each film, people gave ratings of interest, confusion, and their relevant appraisals. Expertise was measured with a preliminar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 40 publications
(56 reference statements)
1
51
0
1
Order By: Relevance
“…Curious people were observed by others to be less anxious, timid, defensive, and concerned about uncertainty, fitting with theoretical accounts that curiosity is generated by beliefs that novelty, complexity, and uncertainty are desirable (novelty potential) and any distress evoked by the events will be manageable (coping potential; Silvia, , ). Prior support for this appraisal model has been limited to artificial laboratory stimuli, including time spent viewing random polygons, art, poetry, and movie clips (Connelly, ; Silvia, , ; Silvia & Berg, ; Turner & Silvia, ). The current study also extends a small body of work suggesting that curious people report being less anxious during initial encounters with strangers (Kashdan & Roberts, , ) and less likely to respond to angry feelings with aggressive behavior (Kashdan et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curious people were observed by others to be less anxious, timid, defensive, and concerned about uncertainty, fitting with theoretical accounts that curiosity is generated by beliefs that novelty, complexity, and uncertainty are desirable (novelty potential) and any distress evoked by the events will be manageable (coping potential; Silvia, , ). Prior support for this appraisal model has been limited to artificial laboratory stimuli, including time spent viewing random polygons, art, poetry, and movie clips (Connelly, ; Silvia, , ; Silvia & Berg, ; Turner & Silvia, ). The current study also extends a small body of work suggesting that curious people report being less anxious during initial encounters with strangers (Kashdan & Roberts, , ) and less likely to respond to angry feelings with aggressive behavior (Kashdan et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Curious people have been shown to be more likely to uncover novelty in their environment (novelty potential), and when they do, they report greater confidence that they can handle unwanted emotions and thoughts elicited by these events (coping potential; Silvia, 2006Silvia, , 2008Silvia, Henson, & Templin, 2009;Spielberger & Starr, 1994). An appraisal model has been useful in explaining why curious people are more likely to visually explore complex polygons, disturbing art, cognitively challenging books, unusual movies, and abstract poetry (Connelly, 2011;Silvia, 2005Silvia, , 2006Silvia & Berg, 2011;Turner & Silvia, 2006).…”
mentioning
confidence: 99%
“…Several studies, for example, have found that experts find art more interesting (e.g., Millis, 2001;Silvia, 2006a). Only one study has considered confusion (Silvia & Berg, 2011): people with more knowledge about film found excerpts from submissions to a local film festival more interesting and less confusing.…”
mentioning
confidence: 99%
“…While fundamentally interesting for the same reasons as other forms of narrative (Silvia & Berg, 2011), films may be special for several reasons: they are more complex but also more comprehensible, they contain visual and auditory information that are rich in detail and vividness, and they have narrative structure (Green, Brock, & Kaufman, 2004). The very reasons that make films more engaging than texts, as seen in both of our experiments, may be the ones that encourage the acquisition of content from them, regardless of whether this content is accurate or inaccurate.…”
Section: Discussionmentioning
confidence: 99%
“…The construct of interest can be described as the intersection of novelty, complexity, and comprehensibility (Silvia, 2008;Silvia & Kashdan, 2009;Silvia & Berg, 2011). When something is new and complex, but not so complex as to be incomprehensible, it is likely to be interesting.…”
Section: Engagementmentioning
confidence: 99%